Formulating The Principle Of Intermediary Liability Based On John Rawls' Distributive Justice - Maslihati Nur Hidayati; Agus Surono; Tubagus Achmad Darodjat (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
The accelerated evolution of the digital economy in Indonesia underscores the limitations of the safe harbor model in intermediary liability regulations, which are presently reactive in nature. The prevailing legal framework, chiefly rooted in the Electronic Information and Transactions Law (ITE Law) and Minister of Communication and Information Technology Regulation No. 5/2020, has a propensity to confer procedural immunity upon marketplace platforms by allocating the risk and the onus of proof to consumers and small traders, thereby engendering a state of structural injustice. The present study identifies the issue of how to reformulate the principle of intermediary liability so as to align with John Rawls' distributive justice, which emphasises active protection for the most vulnerable. Utilising the framework of normative legal research methodologies, a comprehensive examination was undertaken of the pertinent regulations, employing the critical lens of Rawls' theory of justice. The results of the study propose a transformation from a passive notice-and-takedown approach to a proactive model based on five principles: proportional duty of care, public transparency on moderation and algorithms, no-fault recovery mechanisms for risk redistribution, inclusive verification for micro-sellers, and independent audits to prevent algorithmic discrimination. The objective is to transform intermediary liability into a proactive instrument of justice, thereby ensuring that platforms play a role in maintaining a digital ecosystem that is both fair and safe for all.